Exploring sustainability accounting education in the digital era with sustainability leadership as a moderating factor using a two-stage approach PLS-SEM–ANN - Al-Hazaima, Huthaifa; Alduneibat, Khalid Ali; Alhasnawi, Mushtaq Yousif; Alshdaifat, Sajead Mowafaq; Guojing, Hu; Al-Shbiel, Seif Obeid (Springer Nature, 2025)
This study aims to investigate the interrelationships among digital literacy, AI adoption, institutional image, social innovation, and sustainability accounting education in Chinese higher education institutions. Study’s framework was developed by integrating Technology Acceptance Model (TAM), Diffusion of Innovations (DOI) theory, and the Institutional Theory to guide analysing research factors. Two-stage analytical approach was employed - Partial Least Squares Structural Equation Modelling (PLS-SEM) followed by Artificial Neural Network (ANN) approach. Research data were collected through distributing 500 questionnaires, of which 375 valid responses, comprising 75% response. Findings revealed that digital literacy promotes critical connection with sustainability challenges, AI adoption improves personalized learning opportunities and access to real-time environmental data. Universities with a sustainability-oriented image are more likely to entrench sustainability principles into their curricula. Social innovation, promoting collaboration and participatory learning, is perceived as a key player in facilitating sustainability education. Moreover, sustainability leadership is a significant competency that aids in facilitating the responsible integration of technology with sustainability principles. This study provides both theoretical and practical insights for Higher Education Institutions seeking to enhance sustainability education, in addition it contributes to further technological and institutional environment knowledge to shape sustainability education.